Proximity programs for integrated rural development, and its role in moving the local development programs case study of Mila city (2009-2014) - HAREGE, MASBAH (Milev Journal of Research and Studies, 2015)
This study sought to the role of the proximity programs for integrated rural development, to moving and promoting the local development in rural spaces of Mila city during the period (2009-2014), for that we have tried to limiting the various economic and social effects that can made it by these programs in field, then analyzed depending on a number of indicators. Where it show us later the positive of these programs and its field importance for the inhabitants of rural areas, and highlights through the installation of the population and the stability of the rural community as a result of improving living conditions for them (the provision of housing, open roads and pathways, remedy, teaching, security ...) something that individuals were allowed to return to earth service, it has led to a boom in family agriculture (animal husbandry, cultivation of fruits, local symbols ...), and reflected positively on the lives of individuals through improved incomes. However, this local dynamic source proximity programs remain hampered by some of the obstacles that limit their advantages, and perhaps the most important of which is twice the percentage of completion of programs and therefore call on the need to involve the real integration of the various sectors, funding and implementation of them, with the censor effective in this area by the competent local authorities.